Peran Musik Taylor Swift terhadap Mood pada Mahasiswa UIN Antasari dalam Mengerjakan Skripsi - Hidayati, Rizkia; Mawaddah, Wafa'; Dartanyan, Kinanti (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2024)
This research aims to determine the influence of Taylor Swift's music on the mood of UIN Antasari Banjarmasin students in working on their thesis. This research uses an experimental method with a true experimental design pretest-posttest control group design. The control group showed a slight increase in mood from pretest to posttest, from pretest and posttest also showed little change, which may indicate variations in mood changes between individuals in this group. On the other hand, the treatment group showed a more significant improvement in mood from pretest to posttest, with an average of. The standard deviation also showed considerable change, suggesting that responses to Taylor Swift's music may vary quite a bit among college students.